Typification of names in the neotropical genus Luehea (Malvaceae: Grewioideae) - Gerace, Samuele; Bovini, Massimo G.; Peruzzi, Lorenzo; Baumgratz, José Fernando A. (Phytotaxa, 2022)
We present a review of nomenclatural types for the names given to 19 Luehea species and one variety (L. candicans, L. conwentzii, L. densiflora, L. divaricata, L. eichleri, L. ferruginea, L. grandiflora, L. hoehnei, L. laxiflora, L. macrophylla, L. microphylla, L. ochrophylla, L. paniculata, L. parvifolia, L. platypetala, L. rufescens, L. speciosa, L. uniflora, L. uniflora var. gracilis and L. villosa), including one neotypification, nine lectotypifications and seven second-step lectotypifications.